Comparison of immediate effects of sling-based manual therapy on specific spine levels in subjects with neck pain and forward head posture: a randomized clinical trial - Kim, Dae-Hyun; Kim, Suhn-Yeop (Disability and rehabilitation, 2020)
Forward head posture is identified as the flexion of the lower cervical spine along with the extension of the upper cervical spine, with an overall increase in the cervical curve. This study aimed to compare the immediate effect of upper-cervical level and cervicothoracic junction level manual therapy on head posture, cervical range of motion and muscle activity of the subjects with forward head posture. A total 22 subjects with chronic neck pain (numeric pain rating scale >3, forward head posture: cranio-vertebral angle <51°) participated in the study and were randomly allocated into the upper-cervical ( = 11) and cervicothoracic junction ( = 11) groups. Cranio-vertebral angle, cervical range of motion, and electromyography amplitude during performance of the craniocervical flexion test were measured before and immediately after the intervention. There were no significant main effects for the group by time outcome score of craniovertebral angle and electromyography amplitude. However, in the range of motion of the cervical area, the cervicothoracic junction group showed a significant increase in extension and right rotation than the upper-cervical group ( < 0.05). Moreover, in both groups, the electromyography amplitude of the sternocleidomastoid muscle was significantly reduced after intervention. The electromyography amplitude of the anterior scalene muscle in only the cervicothoracic junction group was significantly reduced after intervention ( < 0.05). Cervicothoracic junction manual therapy improved cervical alignment, cervical mobility (extension, rotation), and muscle recruitment ability in subjects with forward head posture. These observations may partially explain the efficacy of this manual therapy in rehabilitation of individuals with mechanical neck disorder (with forward head posture).Implications for rehabilitationForward head posture is identified as the flexion of the lower cervical spine along with the extension of the upper cervical spine, with an overall increase in the cervical curve.Cervicothoracic area manual therapy in subjects with neck pain and forward head posture better improved the muscle recruitment ability than upper cervical area manual therapy during motor tasks.